Расчётный метод исследования пульсаций давления в сервоприводе регулятора дизеля - Грицюк, Александр Васильевич; Григорьев, Александр Львович; Врублевский, Александр Николаевич; Овчинников, Алексей Александрович (НТУ "ХПИ", 2013)
Analyzed the order of the controller of hydraulic type, equipped with a servo-controlled load-spool. The method to study the steady vibrations arising in the cavities and control elements for operation of the engine.
Keywords: модель линеаризованная; колебания установившиеся; груз-золотник; насос шиберный; клапан рециркуляционный